Optofluidic ring resonator laser with biocompatible liquid gain medium - Yoon, Dong Ki; Lee, Wonsuk (23RD OPTO-ELECTRONICS AND COMMUNICATIONS CONFERENCE (OECC2018), 2018)
An optofluidic laser with biocompatible liquid gain medium, made of riboflavin dissolved in water, has been demonstrated. The proposed laser is based on a glass capillary ring resonator with a high Q-factor.